(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Although people often feel relieved after having shared emotions related to a trauma, there are no clear data showing that trauma-related emotions really are transformed by such act of sharing. Empirical research concerning the effects of verbally sharing emotions, led to contra-intuitive results that are difficult to interpret. This is the case both in experimental social psychology as in clinical research on the prevention of post-traumatic stress disorder. A critical appraisal of these results points out a few vacuums that deserve more attention from research. Questions about the relation between experiential avoidance and sharing of emotions and principally about what a person learnswhenreporting his or her emotions should be examined more carefully.